2004
DOI: 10.1159/000079642
|View full text |Cite
|
Sign up to set email alerts
|

Value of Spirometry in Detecting Volume Restriction in Interstitial Lung Disease Patients

Abstract: Background: Restriction is a typical functional abnormality in interstitial lung disease (ILD) patients, but is not always present, especially in the early stage of the disease. The greater reduction of vital capacity (VC; %pred.) than total lung capacity (TLC; %pred.) is regarded as a typical pattern of lung function disturbances in ILD patients. Study Objectives: To explore the diagnostic value of spirometry in a detection restrictive pattern the relative volume loss assessed by TLC and VC in large series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 16 publications
2
13
0
2
Order By: Relevance
“…Previous investigators have also reported normal lung volumes in the majority of patients with stage I or II sarcoidosis [15,26]. The cause of a restrictive ventilatory defect in sarcoidosis patients may be more complex and respiratory muscle weakness should also be considered [27].…”
Section: Discussionmentioning
confidence: 93%
“…Previous investigators have also reported normal lung volumes in the majority of patients with stage I or II sarcoidosis [15,26]. The cause of a restrictive ventilatory defect in sarcoidosis patients may be more complex and respiratory muscle weakness should also be considered [27].…”
Section: Discussionmentioning
confidence: 93%
“…In a general population, where a reduced total lung capacity is rare, the positive predictive value of this test result will be very small. There is therefore little to be said for measurement of the total lung capacity if a restrictive pattern or mixed pattern is diagnosed on the basis of spirometry alone, unless there is a priori clinical evidence of a condition that might cause lung restriction, such as interstitial lung disease [36]. The underlying principle should be to treat the patient, not the numbers [37].…”
Section: Discussionmentioning
confidence: 99%
“…Still, without medical testing in addition to spirometry, we cannot be sure whether spirometric restriction reflects lung disease. It should be noted that in a case series of patients with documented restrictive lung diseases, the combination of restrictive spirometry and low total lung capacity were quite insensitive [Boros et al 2004]. Thus, if true restrictive lung disease is shown to exist in some employees with restrictive spirometry, all employees may need to have other diagnostic tests performed to assess for interstitial lung disease.…”
Section: Discussionmentioning
confidence: 99%